Teachers’ Strategies Used in Distance Learning during Pandemic Covid – 19 Mtsn 2 Kota Kediri - Isnan Achmad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Due to the arrival of COVID-19 in Indonesia, offline learning shifted to online learning, creating new challenges for both teachers and students. They began using new online platforms for their lessons, including an online meeting platform and WhatsApp groups for sharing information. A qualitative study was conducted by the researcher, who used interviews and documentation to gather data from English teachers at MTs Negeri 2 Kota Kediri. The study involved five teachers as participants. Another research tool used was documentation. The findings showed that ELMA was the main app supporting the learning process, as it allowed for activities like explaining materials, assigning tasks, recording attendance, and assessments. During the pandemic, teachers used ELMA and integrated it with other apps, which proved effective for distance learning. However, despite technology's help in the learning process, the study found that its use was not fully optimized due to issues with network connections and students' comprehension. Nevertheless, teachers were aware of these challenges and implemented strategies to address them, one of which included offering free weekly consultations for students who struggled with lessons. The teachers also applied various strategies to ensure the teaching and learning process ran smoothly